(3hajGJ GdCYjGf hCfHGA CHfGA GdReGfs - (3GHf NdcGf , CMeO Hf eMeO Hf EHQGgje Hf CHj HcQ GdHQecj GdGQHdj, TeS GdOjf CHh GdYHGS,J (B681 (3g` s
(3ChdgG (B:s
(3jbhd GdabjQ CMeO Hf NdcGf QMeg dGdg JYGdi HYO MeO Gddg GdPi JaQO HGdHbGA s
(3BNQgG (B:s
(3HJQLeI (B" (3eMeO Hf YHO GdhdjO Hf CHj gGTe GdeYQha HZdGe KYdH (B" (3hBNQ eG ajg jbGd gdG (B: (3HGhQO hCHjhQO hefgG CHh GdYHGS GdeXaQ GdCHjhQOi GdTGYQ GdBJi PcQg Ef TGA Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B220 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B59s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs